THE PSYCHOLOGICAL MANAGEMENT OF EDUCATION IN IMPROVING THE BALANCE BETWEEN ACADEMIC ACHIEVEMENT AND STUDENT MENTAL WELL-BEING - Suryapermana, Nana; Nadhirah, Yahdinil Firda (Yayasan Education and Social Center, 2025)
This study aims to analyze the management of educational psychology in improving the balance between academic achievement and mental well-being of students at the Faculty of Tarbiyah and Teacher Training, UIN Sultan Maulana Hasanuddin Banten. This study employs a qualitative method with in-depth interviews and observations of students under academic pressure as a means of data collection. According to the study's findings, the main element influencing students' mental health was academic pressure—that which results from deadlines and assignments piling on. In addition, good social relationships, a healthy lifestyle, and guidance and counselling services were also found to play an important role in maintaining this balance. Social support from peers, family, and lecturers helped students cope with academic stress, while a healthy lifestyle supported their mental health. The academic performance of students can be positively influenced by the reduction of anxiety and stress that can be achieved through the provision of effective guidance and counselling services. This investigation underscores the significance of psychological support in maintaining the equilibrium between students' academic performance and mental health.